Advancing IBDV diagnostics: a one-step multiplex real-time qRT-PCR for discriminating between vvIBDV and non-vvIBDV viruses, including the newly emerged IBDV variant - Adel, Amany; Zanaty, Ali; Mosaad, Zienab; Selim, Karim; Hagag, Naglaa M.; Badr, Mona; Ellakany, Hany; Shahien, Momtaz; Samy, Ahmed (Frontiers in Veterinary Science, 2024)
The very virulent infectious bursal disease virus (vvIBDV) induces an acute, highly contagious and immunosuppressive disease in younger chicken causing massive economic losses globally. A major challenge in the field’s clinical diagnosis is distinguishing gross lesions caused by vvIBDV from those induced by classic IBDV (cIBDV), commonly used as live attenuated vaccines. This study introduces a one-step multiplex real-time PCR assay designed to distinguish between vvIBDV and non-vvIBDV viruses. Via simultaneously targeting the VP2 sequence for vvIBDV detection and the VP1 sequence for non-vvIBDV identification, including classic, American variant and the recently emerged novel variant IBDV (nvarIBDV), the assay’s specificity was validated against common avian viral diseases and nonspecific IBDV strains without any observed cross-reactions. It effectively differentiated between vvIBDV and non-vvIBDV field samples, including nvarIBDV, as confirmed by genotyping based on VP2 sequencing. The assay demonstrated a limit of detection ranging from 1.9×1010 to 103 DNA copies for vvIBDV-VP2, 9.2×1010 to 103 DNA copies for classic strains, and 1.2×1011 to 104 DNA copies for nvarIBDV in VP1 detection of non-vvIBDV. In conclusion, this study presents a specific, sensitive, and straight forward multiplex real-time PCR assay.